Doubly Outsiders: Pre-war Greek-Australian Migrants and their Socialist Ideals - Nicolacopoulos, Toula; Vassilacopoulos, George (Études helléniques / Hellenic Studies, 2002)
This text invites us into the world of Greek immigrants to Australia in the thirties and forties. The author describes how their political commitment to the Communist party in particular led them to define their identity quite differently. The authors quote interviews with witnesses or participants so that we hear the voices of these brace immigrants.